Sustained Improvement in Tracheal Intubation Safety Across a 15-Center Quality-Improvement Collaborative: An Interventional Study From the National Emergency Airway Registry for Children Investigators*. Issue 2 (11th November 2020) - Nishisaki, Akira; Lee, Anthony; Li, Simon; Sanders, Ronald C.; Brown, Calvin A.; Rehder, Kyle J.; Napolitano, Natalie; Montgomery, Vicki L.; Adu-Darko, Michelle; Bysani, G. Kris; Harwayne-Gidansky, Ilana; Howell, Joy D.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: To evaluate the effect of a tracheal intubation safety bundle on adverse tracheal intubation-associated events across 15 PICUs. Design: Multicenter time-series study. Setting: PICUs in the United States. Patients: All patients received tracheal intubations in ICUs. Interventions: We implemented a tracheal intubation safety bundle as a quality-improvement intervention that includes: 1) quarterly site benchmark performance report and 2) airway safety checklists (preprocedure risk factor, approach, and role planning, preprocedure bedside "time-out, " and immediate postprocedure debriefing). We define each quality-improvement phase as baseline (–24 to –12 mo before checklist implementation), benchmark performance reporting only (–12 to 0 mo before checklist implementation), implementation (checklist implementation start to time achieving > 80% bundle adherence), early bundle adherence (0–12 mo), and sustained (late) bundle adherence (12–24 mo). Bundle adherence was defined a priori as greater than 80% of checklist use for tracheal intubations for 3 consecutive months. Measurements and Main Results: The primary outcome was the adverse tracheal intubation-associated event, and secondary outcomes included severe tracheal intubation-associated events, multiple tracheal intubation attempts, and hypoxemia less than 80%. From January 2013 to December 2015, out of 19 participating PICUs, 15 ICUs (79%) achieved bundle adherence. Among the 15 ICUs, the adverse tracheal intubation-associated event rates were baseline phase: 217/1, 241 (17.5%), benchmark reporting only phase: 257/1, 750 (14.7%), early 0–12 month complete bundle compliance phase: 247/1, 591 (15.5%), and late 12–24 month complete bundle compliance phase: 137/1, 002 (13.7%). After adjusting for patient characteristics and clustering by site, the adverse tracheal intubation-associated event rate significantly decreased compared with baseline: benchmark: odds ratio, 0.83 (0.72–0.97; p = 0.016); early bundle: odds ratio, 0.80 (0.63–1.02; p = 0.074); and late bundle odds ratio, 0.63 (0.47–0.83; p = 0.001). Conclusions: Effective implementation of a quality-improvement bundle was associated with a decrease in the adverse tracheal intubation-associated event that was sustained for 24 months.